{ x 2 + y x y = 3 3 6 y 2 + x x y = 1 1 2
x and y are positive number satisfying the system of equations above. Find x + y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
good observation..+1
Log in to reply
Thanks... :-)
nice manipulation there
I did about the same thing by substituting a=\sqrt(x) and b=\sqrt(y) to get an equation in a and b which was more easily solvable.
Relevant wiki: System of Equations - Problem Solving - Intermediate
Let x = a y , a > 0 . Then as x , y > 0 the system of equations can be written as
a 2 y 2 + y a y 2 = 3 3 6 ⟹ y 2 ( a 2 + a ) = 3 3 6 and
y 2 + a y a y 2 = 1 1 2 ⟹ y 2 ( 1 + a a ) = 1 1 2 .
From this system we see that
a 2 + a = 3 ( 1 + a a ) ⟹ a 2 − 3 a a + a − 3 = 0
⟹ a a ( a − 3 ) + ( a − 3 ) = 0 ⟹ ( a a + 1 ) ( a − 3 ) = 0 .
As a > 0 we cannot have a a = − 1 so we conclude that a − 3 = 0 ⟹ a = 9 .
So y 2 = a 2 + a 3 3 6 = 8 1 + 3 3 3 6 = 4 ⟹ y = 2 ⟹ x = a y = 9 × 2 = 1 8 ,
and thus x + y = 1 8 + 2 = 2 0 .
good solution..+1
Tale x common from first equation, and y common from second equation. Divide to get x = 9 y . Put in the first equation to get y = 2 and x = 1 8
That's what I also did... :-)
Problem Loading...
Note Loading...
Set Loading...
Write them as:
{ x ( x x + y y ) = 3 3 6 y ( x x + y y ) = 1 1 2
Dividing we get y x = 3 ⟹ x = 9 y . Substituting x = 9 y in first equation : ( 9 y ) 2 + y 3 y 9 y 2 = 3 3 6 ⟹ y 2 = 8 4 3 3 6 = 4 ⟹ y = 2
x = 9 y ⟹ x = 9 ( 2 ) = 1 8
∴ x + y = 1 8 + 2 = 2 0